A review of health-related quality of life associated with pneumococcal disease: pooled estimates by age and type of disease. (29th May 2021) - Tang, Zhaoli; Matanock, Almea; Jeon, Seonghye; Leidner, Andrew J
Abstract: Background: Estimates in the research literature on the health-related quality of life (QOL) associated with pneumococcal disease exhibit variation. It complicates the selection of estimates in modeling projects that evaluate the health impact and economic value of the prevention and treatment. This study reviewed the literature and developed pooled QOL estimates associated with pneumococcal disease states. Methods: We searched peer-reviewed literature for studies that reported pneumococcal disease-related QOL estimates. For each study, we extracted QOL estimates and categorized by age group and disease state. QOL estimates were converted to quality-adjusted life-years (QALYs). Pooled QALY estimates were calculated using simple average, sample-size weighting and inverse-variance weighting. Results: From 18 studies, we organized QOL estimates into 20 groups based on age and disease state. We observed the largest within-disease state variations of QALY estimates in meningitis-related disease states compared to other disease states. Across all age–disease state categories, the pooled QALY estimates ranged from 0.39 for meningitis with long-term sequelae among 0- to 18-year-olds, to 1.00 for non-inpatient pneumonia among 0- to 18-year-olds. Conclusions: Our results indicated disparities in QOL estimates associated with pneumococcal disease from the literature. Pooled estimates provided a source of consistency that can be used in future modeling efforts.